DOMAIN-GENERAL AUDITORY PROCESSING EXPLAINS MULTIPLE DIMENSIONS OF L2 ACQUISITION IN ADULTHOOD. Issue 1 (9th March 2022) - Saito, Kazuya; Sun, Hui; Kachlicka, Magdalena; Alayo, John Robert Carvajal; Nakata, Tatsuya; Tierney, Adam
ABSTRACT: In this study, we propose a hypothesis that domain-general auditory processing, a perceptual anchor of L1 acquisition, can serve as the foundation of successful post-pubertal L2 learning. This hypothesis was tested with 139 post-pubertal L2 immersion learners by linking individual differences in auditory discrimination across multiple acoustic dimensions to the segmental, prosodic, lexical, and morphosyntactic dimensions of L2 proficiency. Overall, auditory processing was a primary determinant of a range of participants' proficiency scores, even after biographical factors (experience, age) were controlled for. The link between audition and proficiency was especially clear for L2 learners who had passed beyond the initial phase of immersion (length of residence > 1 year). The findings suggest that greater auditory processing skill benefits post-pubertal L2 learners immersed in naturalistic settings for a sufficient period of time by allowing them to better utilize received input, which results in greater language gains and leads to more advanced L2 proficiency in the long run (similar to L1 acquisition).